O estabelecimento da função discriminativa de respostas e sua participação de classe de estímulos equivalentes - Santos, Lilian Evelin dos (2005)
The present study was a replication of Dymond & Barnes (1994). The study aimed: (a) to verify if the establishment of a pattern of responding as a discriminative stimulus, consistently paired with a stimulus that belonged to a class of equivalent stimuli, would establish the pattern of responding as a member of the same equivalence class, and (b) to verify if the other stimuli of the stimulus class would control responding as a discriminative stimulus, through the insertion of the response pattern in the class. The experimental procedure had 4 phases: (1) a conditional discrimination training and tests for the emergence of two equivalence classes of 3 stimuli (A1, B1, C1 and A2, B2, C2); (2) a self-discrimination training where two distinct response patterns (clicking or not clicking a mouse, in a 5s period) each one systematically paired with one stimulus of each of the equivalence classes (B1 or B2) were established as conditional stimuli controlling the discriminative function of two stimuli (B1 and B2); (3) Test 1: of the possible control of the self-discrimination response over new stimuli, where it was tested if the response patterns with the mouse also controlled the choice between two other stimuli of the equivalence class (C1 and C2), which were never before paired with responding with the mouse; and (4) Test 2: of the possible control, by the stimuli of the equivalence class, over the pattern of responding with the mouse, where it was tested if a choice of either C1 or C2 was followed by responding / not responding with the mouse. Of the 11 adults who started the experiment, 6 completed the study: the performance of 4 of these 6 participants on Test 1 and of 3 of them on Test 2 were successful. Results were similar to the ones found by Dymond & Barnes (1994), suggesting that: (a) response patterns may acquire behavioral functions as stimuli and may become part of equivalence stimulus classes, and (b) stimuli that are part of a equivalent stimulus class may share behavioral functions, because of a history of differential reinforcement related to only one member of the stimulus class